Histologically Diverse BAP1-Deficient Melanocytic Tumors in a Patient With BAP1 Tumor Predisposition Syndrome. (November 2020) - Louw, Amber; Creaney, Jenette; Thomas, Anitha; Van Vliet, Chris; Harvey, Nathan Tobias; Wood, Benjamin Andrew; Mesbah Ardakani, Nima
Abstract : Abstract: BRCA1-associated protein-1 (BAP1)-deficient cutaneous tumors are common in patients with BAP1 tumor predisposition syndrome, frequently presenting before other associated neoplasms, and can serve as an early marker to identify individuals with this disease. The typical lesions are dermal based and composed of a combination of larger epithelioid melanocytes with abundant glassy cytoplasm and smaller cells resembling those of a conventional nevus. There is often a component of interspersed lymphocytes. However, BAP1-deficient melanocytic tumors can show a spectrum of histologic appearances, ranging from lesions with pure epithelioid, pure conventional nevus, or rhabdoid cells and tumors with an intraepidermal component. To demonstrate such morphologic variation, we present a case of a 50-year-old woman with multiple histologically diverse BAP1-deficient melanocytic tumors and germline BAP1 mutation, identified after a diagnosis of pleural mesothelioma. We also discuss the pathogenesis and potential histopathological and clinical indications of germline versus sporadic etiology in the assessment of BAP1-deficient melanocytic tumors.